2021
DOI: 10.1111/ina.12829
|View full text |Cite
|
Sign up to set email alerts
|

The effects of paints and moisture content on the indoor air emissions from pinewood ( Pinus sylvestris ) boards

Abstract: The emissions of volatile organic compounds (VOCs) from building materials may significantly contribute to indoor air pollution, and VOCs have been associated with odor annoyance and adverse health effects. Wood materials together with coatings are commonly used indoors for furniture and large surfaces such as walls, floors, and ceilings. This leads to high surface‐to‐volume ratios, and therefore, these materials may participate remarkably to the VOC levels of indoor environment. We studied emissions of VOCs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Compounds in the chemical classes of bicyclic monoterpene, monocyclic monoterpene, acyclic monoterpene, monoterpenoid ketone, monoterpenoid aldehyde, aliphatic aldehyde, alcohol, acid, and phenol ethers were found. These results represent the volatile fraction of extractives in pine species and essential oils thereof, and the detected compounds are in alignment with reported results [17,34,[36][37][38][39], with the exception of myrtenal and 1-octanol. The occurrence of both compounds can, however, be expected due to degradation/conversion processes in plant species [12,40,41] as they were also detected previously by GC-O [42,43].…”
Section: Discussionsupporting
confidence: 91%
“…Compounds in the chemical classes of bicyclic monoterpene, monocyclic monoterpene, acyclic monoterpene, monoterpenoid ketone, monoterpenoid aldehyde, aliphatic aldehyde, alcohol, acid, and phenol ethers were found. These results represent the volatile fraction of extractives in pine species and essential oils thereof, and the detected compounds are in alignment with reported results [17,34,[36][37][38][39], with the exception of myrtenal and 1-octanol. The occurrence of both compounds can, however, be expected due to degradation/conversion processes in plant species [12,40,41] as they were also detected previously by GC-O [42,43].…”
Section: Discussionsupporting
confidence: 91%
“…Moisture content is also a well-known key parameter influencing overall coating quality and its service life as a function of species. In a past study, it was found that a lower moisture content of a unit increased VOCs emission such as aldehydes and methanol, whereas a higher moisture content resulted in more terpene emissions [38].…”
Section: Vocs Emission From Different Furniture Products and Materialsmentioning
confidence: 99%
“…76–86 New furniture often produces higher emissions of these species, which tend to decrease as it ages. 76,79 Published emission rates from wood and paint for formaldehyde, acetaldehyde, propanal, butanal, pentanal, hexanal, heptanal, octanal, nonanal and decanal 76,79,81 have been averaged and added into the model informed by the surface-area to volume ratio of wooden and painted materials in a typical kitchen, 29,61,87 and are provided in Table S1 †. These aldehyde emission rates are assumed to remain constant throughout the simulation.…”
Section: Methodsmentioning
confidence: 99%
“…Wood and paint are commonly found in homes, and are known to emit indoor air pollutants, primarily short and long-chained aldehydes. [76][77][78][79][80][81][82][83][84][85][86] New furniture oen produces higher emissions of these species, which tend to decrease as it ages. 76,79 Published emission rates from wood and paint for formaldehyde, acetaldehyde, propanal, butanal, pentanal, hexanal, heptanal, octanal, nonanal and decanal 76,79,81 have been averaged and added into the model informed by the surface-area to volume ratio of wooden and painted materials in a typical kitchen, 29,61,87 and are provided in Table S1.…”
Section: The Indoor Chemical Model In Pythonmentioning
confidence: 99%